Role of Employee’s Perception on Manager's Behaviour and Career Support in Building Cordial Relation between Managers and Subordinates (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Employees are the key component of any business organization. Job satisfaction of the employees and employee turnover in a firm largely depends on the intensity of healthy relationship between the supervisor and his subordinates. This study aims to examine the role of behavioral attributes of managers in building a cordial relation between manager and subordinate. Further, the study intended to explore the manager’s career support and its effect on building a cordial relation between manager and subordinate. Data for the seven identified factors were collected from 149 IT professionals in the state of Kerala. Simple and step wise regression analysis were applied to study the effect of behavioral attributes on cordial relation. The result reveals that when studied independently, each behavioural attribute have a positive effect on cordial relationship with the manager. But it is found that when these variables were studied collectively, forgiveness doesn’t have any influence on cordial relationship with the manager. The study explores the importance of managers behaviour in building a cordial relationship between managers and employees.